Two new species of groundwater amphipods of the genus Niphargus Schiödte, 1849 from northwestern Iran - Mamaghani-Shishvan, Mahmoud; Esmaeili-Rineh, Somayeh (European Journal of Taxonomy, 2019)
This study was conducted to describe and illustrate two new species of groundwater amphipods from the northern parts of the Zagros Mountains in West Azerbaijan Province, Iran. Mitochondrial (COI) and nuclear (28S rDNA) fragments as well as several morphological traits were used to characterize Niphargus urmiensis sp. nov. and Niphargus fiseri sp. nov. The phylogenetic analyses showed that the nucleotide differences between the recently described species and their close allies are attributed to their distinctiveness. The molecular analysis also introduced that the new species are placed within the clade comprising Iranian species as a sister taxon. The genetic distances between N. urmiensis sp. nov. and N. fiseri sp. nov. are 7.6% and 1.6%, respectively based on the COI and 28S rDNA gene fragments.